2018
DOI: 10.4314/ovj.v8i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of nitric oxide and increase in diastolic blood pressure are two events that affect renal function in dogs with pituitary dependent hyperadrenocorticism

Abstract: Hyperadrenocorticism is a frequent disease in dogs. The excess of circulating cortisol affects different organs and metabolic pathways, producing severe adverse effects that endanger the animal’s life. Among these effects, hypertension and renal damage can be mentioned. A group of 20 dogs with pituitary dependent hyperadrenocorticism (PDH) and 12 control dogs were used to study the following parameters: cortisol and nitric oxide (NO nit/nit) concentrations, diastolic and systolic blood pressure, renal artery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…This observation warrant monitoring of renal function and systemic hypertension control (Smets et al 2012b). Moreover, other studies have shown that proteinuria is directly correlated with blood pressure (Vidal et al 2018), and that HAC initial treatment with trilostane does not seem to be enough to normalize altered cardiovascular parameters in dogs (Soares et al 2016). In this scenario, it is important to note that the overexpression of the 11β-hydroxysteroid desidrogenase-1 enzyme in visceral adipose tissue of HAC patients could play a role in the maintenance of hypercortisolism in dogs with HAC (Miceli et al 2018).…”
Section: Discussionmentioning
confidence: 82%
“…This observation warrant monitoring of renal function and systemic hypertension control (Smets et al 2012b). Moreover, other studies have shown that proteinuria is directly correlated with blood pressure (Vidal et al 2018), and that HAC initial treatment with trilostane does not seem to be enough to normalize altered cardiovascular parameters in dogs (Soares et al 2016). In this scenario, it is important to note that the overexpression of the 11β-hydroxysteroid desidrogenase-1 enzyme in visceral adipose tissue of HAC patients could play a role in the maintenance of hypercortisolism in dogs with HAC (Miceli et al 2018).…”
Section: Discussionmentioning
confidence: 82%
“…Descriptive statistics of the hematological, biochemical, and urinary variables studied Systemic hypertension is highly prevalent in both humans and dogs with hypercortisolism. [3][4][5][6][7][11][12][13][14][26][27][28][29] However, few studies have focused on the prevalence and risks factors for SH in dogs with naturally occurring HAC. In our study, the prevalence of SH was high (82%) and similar to data (70-85%) from people with CS.…”
Section: Systolic Blood Pressurementioning
confidence: 99%
“…2 Chronic hypercortisolism might lead to several complications such as diabetes mellitus (DM), systemic hypertension (SH), proteinuria, glomerulosclerosis, pancreatitis, gallbladder mucocele, increased susceptibility to infections, or pulmonary thromboembolism among others, both in humans and dogs. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Systemic hypertension associated with hypercortisolism is common in people, affecting 70%-85% of the patients. [4][5][6][7][8] The pathophysiological mechanisms for hypertension in HAC are incompletely understood, but in people a multifactorial model has been proposed with many pathways involved: the renin-angiotensin system, an increased mineralocorticoid activity, the sympathetic nervous system, the vasoregulatory system, metabolic factors, vascular remodeling and sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations